The Students' Emotional Maturity and Learning Motivation through Distance Learning During Covid-19 Outbreak - Ika Rifqiawati; Yolanda Ade Saputri; Hesti Oktaviani; Shifa Nurrohmah; Tri Asih Handayani (International Journal of Biology Education Towards Sustainable Development, 2021)
This research aimed to determine the emotional maturity and learning motivation of students through distance learning. The method used in this research is the quantitative method with survey technique. The data collection technique used a non-test technique with an online questionnaire instrument. The participants in this study included 35 Indonesian High School Student in Indonesia, which represented the accreditation criteria. The average value of students' emotional maturity during the Covid-19 pandemic as a whole was in a good category, with a score of 61.6%. This result shows that high school students with an age range of 15-18 years have a relatively good level of emotional maturity even though they are in distance learning adjustments due to Covid-19. Furthermore, the average value of student learning motivation is in a good category, with 66.5%, which shows that students can maintain learning motivation even in distance learning. Therefore, we can conclude that emotional maturity and learning motivation are still in the good category because students are still not familiar with distance learning, which is quite different from offline learning. Researchers offer suggestions to increase emotional maturity and learning motivation to increase teacher participation and the quality of parenting in distance learning. Students must be good at positive thinking and be themselves in adapting to the new environment.